SIFAT KAPASITANSI PARALEL, INDUKTANSI PARALEL, DAN KONDUKTANSI BISKUIT (KERAS) DALAM KEMASAN ALUMUNIUM FOIL DAN PLASTIK - Erna Rusliana M Saleh (Jurnal Biofisika, 2012)
Knowledge of the dielectric properties of food is very important in research, modeling and development of thermal treatment. Associated with biscuits, crackers knowledge of dielectric properties will be useful for many applications for them to predict future food  kadaluarsanya.  Terdapat  three  dielectric  parameters  measured  were  parallel capacitance , inductance and parallel conductance  on biscuits (hard) with aluminum foil and plastic packaging . The third parameter to measure the dielectric used HIOKI 3532-50  LCR  LCR  -  meter  Hitester  with  pegukuran  frequency  42  Hz  -  5  MHz  in constant current (Constant Current) 1.0 . Results parallel capacitance and inductance measurement parallel pattern looks biscuits decreased with increasing measurement frequency, while the conductance ascending pattern seen with increasing frequency.   Biscuits  with  aluminum  foil  packaging  has  a  parallel  capacitance  value  7x10-6 to 22x10-4 Farad,  parallel  inductance  0.000151  to  3.089  x10 9 and  conductance 0.082533 to 22.285529 Siemens. While packing biscuits with platik have capacitance values  5x10-6 to 2.98 x 10-4 Farad, parallel inductance 0.000216 to 236.026 x 10 9 and conductance 0.073310 to 31.210734 Siemens